Dissolution and separation of brominated epoxy resin of waste printed circuit boards by using di-methyl formamide - Verma H.R.; Singh K.K.; Mankhand T.R. (My University, 2025)
Present work investigates the effect of various parameters on the optimum dissolution of brominated epoxy resin (BER) from waste printed circuit boards (WPCBs) and separation of its different components (copper foil, glass fiber, solder mask etc.) by using dimethylformamide (DMF). Studies revealed that high temperature, high WPCB:DMF ratio and small size of fed WPCBs results in quicker dissolution of BER leading to efficient delamination and separation of WPCBs. Optimized condition ensuing most effective separation of WPCBs into copper foil, solder mask and glass fiber were- temperature- 135 °C, WPCB:DMF ratio- 300 g/L, WPCB size-1 cm × 1 cm, time- 4h. Under optimized conditions WPCBs of 2 cm × 2 cm and 3 cm × 3 cm were delaminated into copper foil and glass fiber in 180 and 240 min, respectively. Strong hydrogen bond formation affinity of DMF, enhanced vibrations and breakage of internal van der Waals’ bonds of BER at elevated temperature are responsible for hydrogen bonding between BER and DMF, leading to the dissolution of BER. The spent DMF is regenerated by using rotary decompression evaporation and analyzed by nuclear magnetic resonance spectroscopy, Fourier transform infra-red spectroscopy (FT-IR). The efficiency of regenerated DMF to dissolve BER is similar to unused DMF even after five usage cycles. Scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDS) and FT-IR technique have been used for quantitate composition and chemical structure analysis of residue obtained after evaporation. This novel and simple technique possess the capability of sorting of different components of WPCBs, recycling of used DMF, separation of BER and simultaneously reduces the cost of operation, effluent generation leading to cleaner processing of WPCBs. © 2016 Elsevier Ltd